A proof of concept on real-time air quality monitoring system - Selvarajah, Ruban; Ibrahim, Noraini; Saringat, Mohd Zainuri (Penerbit UTHM, 2017)
According to the Department of Environment Malaysia, Air Pollutant Index (API) is an indicator for the air quality status at any particular area. API is calculated based on average concentration of air pollutants such as Sulphur Dioxide (SO2), Nitrogen Dioxide (NO2), Carbon Monoxide (CO), ground level Ozone (O3) and particulate matter (PM10), each over their respective period of averaging time. A sub-index for each pollutant is determined separately based on a predetermined standard and the highest sub- index is used as the API (Department of Environment Malaysia, 2000). The United States Environmental Protection Agency (US EPA) (2010) defines PM10 as "Inhalable coarse particles," such as those found near roadways and dusty industries, are larger than 2.5 micrometers and smaller than 10 micrometers in diameter (United States Environmental Protection Agency, 2010). Typically, the concentration PM10 is the highest among all pollutants in Malaysia and therefore it determines the API value (APIMS DOE Malaysia, 2015).